Electrochemistry in bicontinuous microemulsions based on control of dynamic solution structures on electrode surfaces. (October 2016) - Kunitake, Masashi; Kuraya, Eisuke; Kato, Dai; Niwa, Osamu; Nishimi, Taisei
Abstract: Bicontinuous microemulsions (BMEs, Winsor III), also called middle-phase microemulsions, are low-viscosity, isotropic, thermodynamically stable, and spontaneously formed mixtures of water, oil, and surfactants. They are unique solution media for electrochemistry. Here, we introduce the recent progress in the electrochemistry of BMEs from their fundamental aspects to their practical applications. Electrochemistry using BMEs has two irreplaceable properties: the coexistence of hydrophilic and lipophilic species with high self-diffusion coefficients; and the dynamic deformation of structures at an oil/water/electrode ternary interface, which is easily changed according to the property of the electrode surface. Electrochemical contact with the micro-saline and oil phases in a BME is alternately or simultaneously achieved by controlling the hydrophilicity and lipophilicity of the electrode surfaces. The selective electrochemical analysis of hydrophilic and lipophilic antioxidants in liquid foods without extraction demonstrated as the use of the unique ternary solution structures of BME on solid surfaces. Graphical abstract: Highlights: Bicontinuous microemulsions (BMEs) are unique solution media for electrochemistry. Electrochemical contact with micro-saline and oil phases in a BME is controlled by an electrode surface. Selective analysis of hydrophilic and lipophilic species in liquid foods is demonstrated.